Photoelastic analysis of matrix stresses around a high modulus sapphire fibre by means of phase-stepping automated polariscope - Zhao, F. M.; Martin, R. D. S.; Hayes, S. A.; Patterson, E. A.; Young, R. J.; Jones, F. R.
The matrix stress field has been quantified and the micromechanics of fragmentation of sapphire fibres in an epoxy matrix have been investigated using phase-stepping photoelasticity and fluorescence spectroscopy. Contour maps of the isochromatic fringe order (related to the difference in principal stresses)have been used to describe in detail the changes in matrix stress field during stress transfer in the presence of a matrix crack and interfacial debonding. The profiles of interfacial shear stress at various levels of applied matrix stress indicate clearly the extent of interfacial debonding. The results show that the matrix crack significantly reduces the efficiency of stress transfer at the interface. The frictional shear stress at the debonded interface has been found experimentally to be 3-10 MPa for a sapphire fibre embedded in the LY5052/HY5052 epoxy system. The relationship between interfacial shear stress and axial fibre stress is discussed. The interfacial shear stress profiles obtained from photoelasticity has been compared to that calculated from the axial fibre stress measured by shifts in fluorescence spectral bands.
Keywords: FRAGMENTATION; DEBONDING; MATRIX CRACK